Epidemiologic characterization of endodontic diagnosis and treatment - Alvarado, Valeska; Sepúlveda, Gabriela; Mariño, Dylan (Applied Sciences in Dentistry, 2020)
Objetive: To characterize the endodontic diagnosis and treatments performed during 2008-2011 at School of Dentistry, University of Andrés Bello, Chile. Methos: Case series study comprising 632 endodontics clinical records, corresponding to 506 patients. Variables included were clinical and radiographic features of the tooth anatomy, and variables related to treatment. Statistics analysis was performed through Stata 11 software. For multivariate analysis, logistic regression model was used, including adjusted Odd ratio; p<0.05 was considered significative. Results: The most frequent diagnosis were pulp necrosis and asymptomatic irreversible pulpitis. Endodontic treatments were more common in women, in upper maxilla, in molars and premolars; in general, the main biomechanical preparation technique is manual and hybrid, except in molars, where mechanized technique is more common; the most used master apical file was file #40, and in upper incisors, #60; lateral condensation obturation technique was the most frequently used. A good prognosis was related with lateral and vertical obturation technique, and absence of soft tissue alterations. Conclusions: This study brought relevant information about working lengths for each root canal for each tooth type. It related tooth type with the technique used for the coronal two-thirds preparation and its instruments, obturation technique and informed about the master file used for each root canal, by means of cross tables. Also, it builds an estimation model for the postoperative prognosis